Qualitative analysis mediated by IRaMuTeQ software: Experiences of yesterday and today in the Brazilian Unified Health System - Marcelo Prado Amaral-Rosa (2021)
The central point is the Brazilian Unified Health System, the largest social inclusion policy in Brazilian history. It focuses on the perceptions of people who experienced Brazilian health before and after the implementation of the system. Objective: the aim was to present analytical nuances of the textual discursive analysis supported by the IRaMuTeQ software on the experiences of Brazilian citizens about yesterday and today of the Unified Health System. Method: it is a qualitative approach research. Participants are public health network users over 60 years of age (n=39). The data collection instrument was the semi-structured interview. The method for data analysis was textual discursive analysis, supported by IRaMuTeQ software. In the software, the basic analyses performed were the descending hierarchical classification and the correspondence Factor Analysis. Results: the main result was the emergence of four final categories: i) suffering with public health; ii) deficiency associated with before and after SUS; iii) improvement and prospects for the future of SUS; and iv) challenges facing neglect with public health. Conclusions: i) the understanding, more precisely in front of the categorization process of the Analysis of Textual Discourse, it is necessary to interpreting all of the data from the Rating of the Hierarchical top-down in the Factor Analysis, correlation, ii) the experiences of yesterday, phase that precedes the implementation of the Brazilian unified health system is directly related to the suffering of the user in the search for care in the public network; and iii) the experiences of today, are loaded with challenges, however, present the positive side of the Unified Health System in the life of the user.